02 Characterising cardiovascular safety profile of muscarinic antagonist, ipratropium. Issue 1 (10th December 2010) - Simmons, K; Khan, J; Hussain, A; Maddock, H L
Abstract : Chronic Obstructive Pulmonary Disease (COPD) is a disease characterised by inflammation of the airways which accounts for the fourth highest cause of global death. The functional role of Muscarinic receptor antagonists such as Ipratropium Bromide (Atrovent) and Tiotropium Bromide (Spiriva) has been shown to successfully improve pulmonary function in COPD patients. Recent studies have associated an increased risk of cardiovascular events in COPD patients currently receiving treatment with Muscarinic receptor antagonists such as Ipratropium (Ogale et al, 2010). The study aimed to investigate the effects of Ipratropium on the myocardium subjected to ischaemia-reperfusion (I/R). Langendorff hearts were subjected to control or I/R in the absence or presence of Ipratropium (1 nM, 10 nM, or 100 nM). Hearts underwent triphenyl tetrazolium staining for infarct size assessment. In further studies cardiac myocytes were isolated and exposed to simulated I/R in the absence or presence of Ipratropium (1 fM–1 mM) and cellular injury was subsequently determined by measurement of live/death ratio and apoptosis using flow cytometry. Administration of Ipratropium (10 nM or 100 nM) throughout reperfusion significantly increased infarct size to risk ratio (%) compared with non-treated controls (62±2%, 74±4% vs 52±3%, control p<0.01, respectively). In isolated myocyte experiments, Ipratopium-treated groups were observed to significantly increase apoptosis and cell death compared to non-treated controls. This is the first pre-clinical study to show that Ipratropium significantly increases myocardial injury when administered during I/R. Further studies are being investigated to determine the mechanism of action of the cardiovascular events associated with certain bronchodilators.